Synergistic development of green building market under government guidance: A case study of Tianjin, China. (15th March 2022) - Qiao, Wanzhen; Dong, Peiwu; Ju, Yanbing
Abstract: Under the restriction of carbon neutral and carbon peak, the development of green building has become the strategic demand of most countries in the world. Despite the rapid development of green building in China, there are still some problems, such as insufficient market development force under the government's leadership, emphasizing design and neglecting operation. In order to realize high-quality synergistic development of green building market, this paper constructs a new synergistic development framework of green building market, establishes a tripartite evolutionary game model including local governments, developers and consumers, uses the analysis tool of evolutionary game theory and synergistic theory to explore the unilateral ESS and the system ESS of green building market. In order to verify the model, this paper adopts a case study method, takes a residential building project in Tianjin, China which has awarded a three-star mark in green building design evaluation as an example for numerical simulation, discusses the influence of government guidance on the system evolution trajectory, demonstrates the interactive process of stakeholders' behavior, and finds out the key factors affecting the system equilibrium strategy. The result shows that (1) the means of government guidance will affect the speed and result of system evolution; (2) the strategy of stakeholders depends on the comparison of costs and benefits; (3) the probability of ideal events is positively correlated with the economic benefits and negatively correlated with incremental cost of green building. This study can provide theoretical guidance for local governments, developers and consumers to make scientific decisions, and provide practical enlightenment for government to play a more active role in green building market.